(untitled) (Progressive Agriculture, 2019)
An experiment was carried out at the field laboratory of the Department of Agricultural Botany, Patuakhali Science and Technology University (PSTU), Patuakhali during the period from January to March, 2012 to study the effect of mugbean genotypes on growth, development, morpho-physiological, yield and yield attributing characters under the agro ecological Zone (AEZ-13) in the region of Southern part of Patuakhali District. Five hybrid genotypes of mugbean viz., Local variety (V1), BARI mung 5(V2), BINA mung 5(V3), BARI mung 6(V4) and BINA mung 8(V5) were used as planting materials for this study. Among the genotypes, BINA mung 5 showed significantly better performance on growth, yield and morpho-physiological characters compare to other genotype during this study while local variety were less efficient among those parameters. As a result, the tallest plant of 57.020 cm higher TDM (72.538 g/plant) and LA (421.152 cm2) were recorded in BINA mung 5 at harvest. BINA mung 5 also had higher number of seeds per pod (13.25), 1000 seeds weight (52.495g), grain yield (1.997t/ha), straw yield (3.660t/ha), biological yield (5.657t/ha) and harvest index (35.303%). On basis of these findings, BINA mung 5 was the most productive variety under the coastal area. Progressive Agriculture 29 (4): 313-319, 2018